If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = -4x Solving 90 = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 90 + 4x = -4x + 4x Combine like terms: -4x + 4x = 0 90 + 4x = 0 Add '-90' to each side of the equation. 90 + -90 + 4x = 0 + -90 Combine like terms: 90 + -90 = 0 0 + 4x = 0 + -90 4x = 0 + -90 Combine like terms: 0 + -90 = -90 4x = -90 Divide each side by '4'. x = -22.5 Simplifying x = -22.5
| x=75(x)+7 | | (6-5i)+(7-2i)= | | 42-3x=12+12x | | 441+b*b=841 | | 3b/100 | | 27-4x=12-7x | | y=5/8=-1/4 | | 11x=-35+4 | | 2(x-6)+2x-10= | | .23x=.94 | | 12y=38x-100 | | 8x-(5x-7)= | | k/12=3 | | 5m-6=8 | | 3y/100 | | 38x+12y=100 | | -8v-5=3v^2 | | 5m+6=8 | | 12x-38y=100 | | 3x/100 | | y(0)-8=2x | | 196+b*b=529 | | (-x+12)-(-4x+2)= | | solve-np-70=40forn | | 4(0)-8=2x | | 03/x3/5 | | x^3=3/16 | | 4ln(7x+4)=12 | | 10x+4=11x | | 20+y=6y | | 9=-h+5h+7 | | 74=2s+(6-2s) |